The Spatial Organization of Long-Term Synaptic Plasticity at the Input Stage of Cerebellum - Mapelli, Jonathan (J Neurosci, 2007)
The spatial organization of long-term synaptic plasticity [long-term potentiation (LTP) and long-term depression (LTD)] is supposed to play a critical role for distributed signal processing in neuronal networks, but its nature remains undetermined in most central circuits. By using multielectrode array recordings, we have reconstructed activation maps of the granular layer in cerebellar slices. LTP and LTD induced by theta-burst stimulation appeared in patches organized in such a way that, on average, LTP was surrounded by LTD. The sign of long-term synaptic plasticity in a given granular layer region was directly correlated with excitation and inversely correlated with inhibition: the most active areas tended to generate LTP, whereas the least active areas tended to generate LTD. Plasticity was almost entirely prevented by application of the NMDA receptor blocker, APV. This suggests that synaptic inhibition, through a control of membrane depolarization, effectively regulates NMDA channel unblock, postsynaptic calcium entry, and the induction of bidirectional synaptic plasticity at the mossy fiber–granule cell relay (Gall et al., 2005). By this mechanism, LTP and LTD could regulate the geometry and contrast of network computations, preprocessing the mossy fiber input to be conveyed to Purkinje cells and molecular layer interneurons.